Court Competence In Administration In Resolving The Land Disputes To The Land - Siti Fatimah Nur Afifah; Zubaida Djaiz Baranyanan; M. Zamroni; Bambang Panji Gunawan (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
The purpose of this study is to describe the competence of the State Administrative Court in handling land disputes. With the existence of a duplicate certificate of ownership originating from two legal aspects there is also a dualism in handling the case, and with the existence of the antinomy of this legal norm, this can further lead to a conflict of competence in adjudicating between the General Court or State Administrative Court in resolving land disputes. This research uses a normative method, in which the sources of legal materials are used by using literature studies, legislation, journals / articles, jurisprudence and books. Significantly this research shows that the competency of Administrative Court becomes a place that should be a reference for legal certainty seekers for the existence of a double certificate that can be tested for validity through the State Administrative Court for the Decree of a State Administration officia.